The Secret To Teen Power - Harrington, Paul (Simon & Schuster, Inc., 2009)
Well, if you've ever had a dream, a secret ambision, a passionate desire or goal, but had no idea how to make it real, then the secret to teen power is for you. The secret has already shpown millions of people all over the world how to change their lives and make their dreams come true. and you can do it too.
Keywords: Non-Fiction